In vivo diffusion measurements as an indication of fetal lung maturation using echo planar imaging at 0.5T. - Moore, R; Strachan, B; Tyler, D; Baker, P; Gowland, P (2001)
The aim of this study was twofold: First, to establish the normal range of fetal lung diffusion values measured during healthy pregnancy; and second, to determine whether fetal lung diffusion could be used as an indication of fetal lung maturity. The apparent diffusion coefficient (ADC), averaged over all 26 subjects with an average gestational age of 29 +/- 6 weeks (mean +/- sd), was found to be 2.0 +/- 0.6 x 10(-9) m(2)/sec (mean +/- sd), but a trend was found indicating that ADC increased with gestational age at the rate of 0.07 x 10(-9) m(2)/sec per week (P = 4 x 10(-5)). To determine the usefulness of this data in predicting lung maturity, a simple three-compartment model was proposed which was comprised of intra-lung amniotic fluid, intra-tissue water, and vascular blood. The relative proportions of each compartment were taken from the literature, and exchange between the compartments was assumed to be minimal. This model predicted the in vivo data reasonably well, and indicated that MR measurements of fetal lung diffusion are a marker for the degree of vascularization of the terminal tubules. Magn Reson Med 45:247-253, 2001.